Evaluation for the production of Azotobacter sp. growth promoter for Coffea arabica crops - Zavala, Jesus (2020)
Biofertilizers are microorganisms that enhance the productivity and health of crops, help nitrogen fixation, solubilize phosphates, produce siderophores and phytohormones. There is a large community of microorganisms that help fertilize the soil, one of them being the genus Azotobacter. The aim of the present research is the evaluation of parameters for potential production of Azotobacter sp on a large scale. 15 soil samples from the Rioja province in San Martin, Peru, were processed for Azotobacter isolation and nitrogen fixing capacity, phytohormone production and phosphate solubilization index were measured. The best growth promoting strain was cultured in batch conditions to evaluate production parameters. Out of the 18 Azotobacter strains isolated, 1I and 1F showed the best results for nitrogen fixation with 2.0496 mgL-1, 1.428 mgL-1, respectively; the 1F strain had the highest phytohormone production with 54.972 mgL-1, followed by 1G strain with 52.526 mgL-1; the highest phosphate solubilization index was shown by 1F strain with 3.0. It was concluded that the best growth promoting strain was 1F and the optimized parameters for scaling production were 120 RPM agitation, ph 7, 30 oC and 1VVM were the highest specific growth rate (µmax) was achieved, compared to the other variable combinations.